Lokus Kendali Internal dan Kemampuan Interpersonal sebagai Prediktor Kesiapan Mengelola Bisnis - Agung Minto Wahyu; Angga Yuni Mantara; Rakhmaditya Dewi Noorrizki (Universitas Diponegoro, 2020)
Students' ability to operate their business will be determined by certain aspects. The aim of this study was to analyze the influence of internal locus of control (X1) and interpersonal ability (X2) on the readiness to manage business (Y). This research uses quantitative methods with linear regression analysis. Subjects were 141 business students. Sampling method that was used in this research was a purposive sampling technique using a Likert scale. Descriptive test results indicate that most students have internal locus of control, interpersonal skills, and readiness to manage businesses that are in the medium category. Partial test shows that X1 has a positive and significant effect on readiness to manage business Y. Variable X2 has a positive and significant effect on Y. Simultaneous results show that X1 and X2 have positive and significant effects on Y. In next research researchers are expected to be able to broaden the scope of the subject and explore further about the independent variables that have the ability to influence the readiness to manage the business. More detailed discussions and suggestions have been discussed in this study.